2008
DOI: 10.1002/clc.20209
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Glomerular Filtration Rate and Survival in Patients Treated with an Implantable Cardioverter Defibrillator

Abstract: Objectives: We explored the association between renal insufficiency (RI) and mortality among patients treated with an implantable cardioverter defibrillator (ICD). Background: Randomized trials have shown improvements in survival among select patients treated with an ICD. Renal insufficiency patients have a high risk of cardiac death; however, it is not clear whether the ICD has a positive effect on survival in this group of patients. Methods: This was a retrospective review of a single-center experience of 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Patients with advanced chronic renal failure on dialysis are known to be at increased risk for sudden cardiac arrest, but the mechanisms underlying this association are not well defined . The association between renal function at the time of initial ICD implantation and subsequent mortality has been previously explored, and most data have suggested an independent association between impaired renal function at the time of initial ICD implantation and subsequent increased mortality , . A meta‐analysis of the MADIT‐I, MADIT‐II, and SCD‐HeFT randomized control trials also demonstrated that patients with a CKD‐EPI eGFR <60 mL/min/1.73 m 2 derived no net mortality benefit from primary prevention ICD implantation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with advanced chronic renal failure on dialysis are known to be at increased risk for sudden cardiac arrest, but the mechanisms underlying this association are not well defined . The association between renal function at the time of initial ICD implantation and subsequent mortality has been previously explored, and most data have suggested an independent association between impaired renal function at the time of initial ICD implantation and subsequent increased mortality , . A meta‐analysis of the MADIT‐I, MADIT‐II, and SCD‐HeFT randomized control trials also demonstrated that patients with a CKD‐EPI eGFR <60 mL/min/1.73 m 2 derived no net mortality benefit from primary prevention ICD implantation …”
Section: Discussionmentioning
confidence: 99%
“…28 The association between renal function at the time of initial ICD implantation and subsequent mortality has been previously explored, and most data have suggested an independent association between impaired renal function at the time of initial ICD implantation and subsequent increased mortality. 8,[13][14][15][16][17][18][19][20] A meta-analysis of the MADIT-I, MADIT-II, and SCD-HeFT randomized control trials also demonstrated that patients with a CKD-EPI eGFR <60 mL/min/1.73 m 2 derived no net mortality benefit from primary prevention ICD implantation. 29 The association between renal function at the time of ICD generator replacement and mortality is less well studied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation